Perilaku Bermain Game Online Terhadap Insomnia Pada Remaja Di Bogor - Nourmayansa Vidya Anggraini; Diah Ratnawati (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: Communication technology is growing rapidly, including the internet. One of the negative impacts is the excessive use of online games. The users are not only from among children but primarily teenagers. Internet use among adolescents aged 15-19 years reaches 91%. Unhealthy internet use has a significant risk, including addiction to online games. Addiction to online games can lead to sleep problems and insomnia. Insomnia is a condition of a person with sleep disturbances to difficulty sleeping.Methods: This study used a non-experimental research design with a cross-sectional approach. The goal is to see whether or not there is a relationship between the dependent and independent variables. The independent variable of this study is the behavior of playing online games in adolescents. The independent variable in this study is the insomnia scale. The sampling technique used in this research is purposive sampling. The sample used is included in the inclusion criteria, namely all students who are actively attending SMAN X Bogor and have cellphones, with the number of samples in this study amounting to 170 students. Data collection using an instrument in the form of a questionnaire. Data analysis was carried out using the SPSS for windows version 25.0 program. Data analysis in this study is the univariate analysis by distributing frequency and proportion to describe the data on the characteristics of respondents age, gender, youth. Meanwhile, we used bivariate analysis to determine the relationship between online game playing behavior and insomnia scale in adolescents at SMAN X Bogor. Analysis using Chi-square test with a significance level of 5%.Results: The result of this study is that there is a relationship between online gaming behavior and insomnia in adolescents.Conclusion: Based on the results of the study, several things that can be recommended are teenagers should limit themselves in playing online games and be able to manage their time to sleep, so they are not disturbed, parents should supervise and schedule teenagers' daily activities, schools should implement rules and sanctions for teenagers who like to fall asleep during lessons to maintain discipline in behavior, nurses should be able to provide counseling to the community and nursing care when dealing with teenagers with online game playing behavior that has affected their sleep patterns.